THE INFLUENCE OF ANTI-STRESS MASSAGE IN KEEPING CAPACITY APNEA (Fiep Bulletin - online, 2015)
This work was mainly aimed at checking on the influence of anti-stress massage in the improvement of the respiratory system through the ability of volunteers to maintain apnea. Implementing the proposed objective was held, initially, a literature that provided the necessary theoretical basis. The research was based on a test administered in 15 male volunteers aged 24 to 49 years, sedentary and stressed. They had to submerge his head in a container of water before and after receiving the anti-stress massage, while one of the researchers has measured with the help of pulse oximeter device (Moriya- MD300C1 and MD300C2) and a stopwatch time that volunteers kept apnea. Data collection was performed by applying the Informed Consent and Informed and by means of a questionnaire adapted EVA. Approximately 86.6% retained and / or increased O² level in the blood, decreased by 80% the level of heart rate per minute (bpm), or relaxed after the massage and 66.7% increased the time after apnea massage. It is concluded that the anti-stress massage had a positive effect on the respiratory system of volunteers.
Keywords: Massage; anti-stress; apnea.